Walden Two with a new preface by the author - Skinner, B. F. (Burrhus Frederic), 1904-1990 (Hackett Publishing, 2005)
This fictional outline of a modern utopia has been a center of controversy ever since its publication in 1948. Set in the United States, it pictures a society in which human problems are solved by a scientific technology of human conduct. It is now widely recognized that great changes must be made in the American way of life. Not only can we not face the rest of the world while consuming and polluting as we do, we cannot for long face ourselves while acknowledging the violence and chaos in which we live. The choice is clear: either we do nothing and allow a miserable and probably catastrophic future to overtake us, or we use our knowledge about human behavior to create a social environment in which we shall live productive and creative lives and do so without jeopardizing the chances that those who follow us will be able to do the same. -Back cover.